Incorpating gamification in a flipped classroom approach: A review of literature - Sulong, Azia; Ibrahim, Abu Bakar; Abas, Ashardi; Abu Bakar, Amal Zunnairah (Jurnal Pendidikan Bitara UPSI, 2021)
This study aimed towards designing and developing an instructional learning module, where it combines flipped classroom approach and gamification. Information obtained through 20 articles reported on the gamified flipped classroom, where the study was conducted from 2015 - 2020. The content analysis method was used to identify the online platform or tools, the impact of gamified flipped classroom on student’s learning and gamification element in a gamified flipped classroom. The results showed that some web platform or tools were employed for gamified flipped classroom practice and year by year, a variety of online platform or tools have been used. The result also showed, the use of gamified flipped classroom yielded positive impact on three (3) aspects; (i)student’s motivation, (ii)engagement; and (iii)achievement. While, point, badges and leaderboard were reported as the most basic elements used in gamifying activity. This paper also proposes the future research on focusing in detailing the gamification for out-class and in-class activities. The findings of this review potentially provide insights for further studies in a gamified flipped classroom approach.